Analytical study of offensive and defensive follow-up West Asian Basketball Championship 2010 (Journal of the College of Basic Education, 2022)
The importance of the research lies in the possibility of changing the results of basketball matches by mastering the offensive and defensive follow-up and investing it by the players as it gives a second chance for the team to score two points after one of the attackers fails to hit the goal, and that most matches decide their results on successful skills on the goal in basketball because the one point that One of the two teams advances it over the other, which makes it a winner in the matches. As for the research problem, it is clear in the weakness of applying the offensive and defensive follow-up, which is below the required level compared to other teams, which leads to wasting follow-up opportunities and losing many points in the match.